184k views
5 votes
Expand and simplify x(x-3)(x+5)

User Eptx
by
6.3k points

1 Answer

3 votes

Answer:

x^3+2x^2-15x

Explanation:

Ohk there various methods and steps which can be followed,but let's simplify

In the first method,

Lets put off the brackets hence we will multiply,simplify the equations in the brackets,which would be as followed:

x(x-3)(x+5)

Let's Start with solving the bracket equation,which would be-

(x-3)(x+5)=x(x+5)-3(x+5)=x^2+5x-3x-15

=x^2+2x-15

While multiplying the above equation we got with `x',we get:

x(x^2+2x-15)=x^3+2x^2-15x(Hence solved)

Or/otherway/otherwise:

x(x-3)(x+5)=[x(x-3)](x+5)=(x^2-3x)(x+5)

=x^2(x+5)-3x(x+5)=x^3+5x^2-3x^2-15x

=x^3+2x^2-15x(Solved)

User Dustin Graham
by
6.3k points